(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper aims to present insights into advance care planning (ACP) research activity in the Italian context. The suggestions presented in this paper are based on a multicentric and multiprofessional research project conducted with people with multiple sclerosis, the ConCure-SM pilot study.The manuscript, after outlining the project phases and characterizing elements, focuses on some aspects considered worthy of attention, specifically: barriers and facilitating elements in ACP research; tools to measure the impact of a ACP; training of health professionals on the topic; and time management in a ACP process.